2011
DOI: 10.1161/atvbaha.111.232975
|View full text |Cite
|
Sign up to set email alerts
|

Directed Differentiation of Skin-Derived Precursors Into Functional Vascular Smooth Muscle Cells

Abstract: Objective-The goal of this study was to characterize the factors and conditions required for smooth muscle cell (SMC)-directed differentiation of Sox2 ϩ multipotent rat and human skin-derived precursors (SKPs) and to define whether they represent a source of fully functional vascular SMCs for applications in vivo. Methods and Results-We found that rat SKPs can differentiate almost exclusively into SMCs by reducing serum concentrations to 0.5% to 2% and plating them at low density. Human SKPs derived from fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 68 publications
(80 reference statements)
2
32
0
Order By: Relevance
“…A previous study 28 reported that SKPs directly differentiate vascular smooth muscle cells with the addition of transforming growth factor A in vivo. However, in our histological analysis of immunofluorescent stained region by PKH26 and antiYCD31 antibody, direct differentiation to vessels of applied SKPs was not confirmed (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 28 reported that SKPs directly differentiate vascular smooth muscle cells with the addition of transforming growth factor A in vivo. However, in our histological analysis of immunofluorescent stained region by PKH26 and antiYCD31 antibody, direct differentiation to vessels of applied SKPs was not confirmed (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac neural crest contributes to the heart stem cell pool 68 and the embryonic branchial arches (where TAp63 is detected) contain mesendodermal cells of neural crest origin that participate to the heart development. 69 As SKPs cells are also derived from the neural crest and can produce functional smooth muscle cells, 70 it would be interesting to determine whether the TAp63-expressing endodermal cells with cardiogenic inductive role 36 have a common embryonic origin with the dermal SKPs and whether the latter could have cardiogenic activity on mesocardiac progenitors. Again, a careful analysis of the microarray and Chip-seq analysis of SKPs cells may be informative.…”
Section: In Tap63mentioning
confidence: 99%
“…98 Thus, alternative cell types, such as skin-derived precursors, ought to be recognized for their potential as VSMC sources as they readily differentiate into VSMCs using the same growth factors required to generate VSMCs from neural crest precursors. 99 Moreover, they have been used to model type II diabetes mellitus in elderly patients, without the need for reprogramming required in iPSC generation, often resulting in erasure of disease-relevant epigenetic modifications. 100 Drug screening may also prove difficult using newly differentiated cells if pharmacotherapy is only required in the later stages of disease because newly differentiated cells will not have been exposed to environmental factors responsible for advancing pathological processes.…”
Section: Challenges In Ipsc-derived Vsmcsmentioning
confidence: 99%